Analysis of Restaurant Tax Online System Policy for optimization of Regional Tax Revenue at DKI Jakarta Provincial Revenue Agency - Bernado Yulianto; Zaman Zaini (IJESS International Journal of Education and Social Science, 2021)
This research is based on the existing phenomena where tax revenues have not been optimal, through the Restaurant Tax Online System policy as one of the efforts in optimizing Local Tax Revenues. Restaurant Tax is one of the local tax revenues that have a large contribution. This research aims to analyze the Restaurant Tax Online System Policy for optimization of Regional Tax Revenues in the Regional Revenue Agency of DKI Jakarta Province. This study uses single cash (single case study), using qualitative methods, data is collected through observations, in-depth interviews, and documentation with the aim of producing the best conclusions and can strengthen the researcher's arguments. The results showed that the policy of the online system of restaurant tax for optimization of local tax revenue has not been implemented optimally, less optimally due to human resources that do not handle Information and Technology (IT), the number of restaurants that still use manual transaction systems, there are still taxpayer concerns about the online system of restaurant taxes, and there are still taxpayers who do not want their business transactions online. The results of the study can be concluded that the Analysis of Restaurant Tax Online System Policy for optimization of Overall Local Tax Revenue is less continuous socialization and the online system method has not been done effectively so that tax revenues have not been optimal.